Prospects for summative evaluation of CAL in higher education - Stephen W. Draper (Association for Learning Technology, 1997)
Summative evaluation is evaluation done after software design and production is complete in order to establish its performance and properties. A prototypical case would be the tables produced in the consumer magazine Which? comparing a considerable range of properties of alternative available products (for example, washing machines) that they have measured in their own trials. Thus summative evaluation is not only done after production; it is typically about comparative measurements done to assist decisions concerning purchase.